The Integration of Pancasila-Based Justice in The Legal Protection of Specific Personal Data in The Digital Era - Raihan Imam Cahya Akbar; Ramlan Ramlan; Ida Nadirah (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The rapid expansion of digital technologies has transformed personal data into a strategic asset, while simultaneously increasing the risk of misuse, particularly concerning specific and sensitive personal data. This article examines the integration of Pancasila-based justice into the legal protection framework for specific personal data in Indonesia. Using a normative juridical method with philosophical and statutory approaches, this study analyzes how the values of Pancasila—especially human dignity, social justice, and democratic governance—are embedded within Law Number 27 of 2022 on Personal Data Protection. The findings reveal that although the Personal Data Protection Law reflects Pancasila values at a normative level, significant challenges remain in its substantive implementation, particularly due to sectoral fragmentation, enforcement limitations, and the asymmetry of power between data controllers and data subjects. This study argues that strengthening the protection of specific personal data requires not only regulatory harmonization but also the reconstruction of enforcement mechanisms grounded in Pancasila-based substantive justice.